PENGARUH KONSENTRASI BINDER DAN LAMA WAKTU PENGUKUSAN TERHADAP KARAKTERISTIK MI SORGUM BEBAS GLUTEN - Elmi Kamsiati; Eka Rahayu; Heny Herawati (AGROINTEK, 2021)
Sorghum noodles were developed from sorghum flour by modifying formulas and processes to overcome the absence of gluten from non-wheat raw material. The presence of gluten in wheat flour gives elasticity and viscosity to the noodles. The function of gluten needs to be replaced with other ingredients to obtain noodles with good texture. Tapioca is a natural starch that acts as a binder and texturizing agent in noodles processing. This study aims is to determine the effect of tapioca proportion and steaming time on the characteristics of sorghum noodles. The study consisted of two stages of research. Preliminary research was conducted to determine the effect of tapioca proportion and steaming duration on the texture of sorghum noodles. The next step was optimizing the treatments to produce the best sorghum noodles. The results showed that the proportion of tapioca and cooking time affect the texture and cooking characteristics of sorghum noodles. Increasing the cooking time would reduce the cooking loss of the noodles. The best sorghum noodles obtained from proportion of  sorghum flour: tapioca 90:10 w/w, with 25 minutes steaming time. That sorgum noodles had 111% rehydration power and 4.095% cooking loss. The noodle colour was L 48.02, a -0.82, b 26.65 and H 91.72. The sorghum noodles had moisture content 5,78%; ash content 2,06%, fat content 0,58%, and protein content 0,69%.